The effect of cognitive and behavioral therapy for insomnia on week-to-week changes in sleepiness and sleep parameters in patients with comorbid insomnia and sleep apnea: a randomized controlled trial. Issue 7 (12th January 2020) - Sweetman, Alexander; McEvoy, R Doug; Smith, Simon; Catcheside, Peter G; Antic, Nick A; Chai-Coetzer, Ching Li; Douglas, James; O'Grady, Amanda; Dunn, Nicola; Robinson, Jan; Paul, Denzil; Williamson, Paul; et al.
Abstract: Study Objectives: While cognitive and behavioral therapy for insomnia (CBTi) is an effective treatment in patients with comorbid moderate and severe obstructive sleep apnea (OSA), there is concern that the bedtime restriction component of CBTi might dangerously exacerbate daytime sleepiness in such patients. We examined randomized controlled trial data to investigate the effect of OSA severity, and pretreatment daytime sleepiness on week-to-week changes in daytime sleepiness and sleep parameters during CBTi and no-treatment control. Methods: One hundred and forty-five patients with untreated physician-diagnosed OSA (apnea–hypopnea index ≥15) and psychologist-diagnosed insomnia (ICSD-3) were randomized to a 4-week CBTi program ( n = 72) or no-treatment control ( n = 73). The Epworth sleepiness scale (ESS) and sleep diaries were completed during pretreatment, weekly CBTi sessions, and posttreatment. Effects of OSA severity, pretreatment daytime sleepiness, and intervention group on weekly changes in daytime sleepiness and sleep parameters were investigated. Results: The CBTi group reported a 15% increase in ESS scores following the first week of bedtime restriction ( M change = 1.3 points, 95% CI = 0.1–2.5, p = 0.031, Cohen's d = 0.27) which immediately returned to pretreatment levels for all subsequent weeks, while sleep parameters gradually improved throughout CBTi. There were no differences in changes in daytime sleepiness during treatment between CBTi and control groups or OSA-severity groups. Higher pretreatment ESS scores were associated with a greater ESS reduction during CBTi. Conclusions: CBTi appears to be a safe and effective treatment in the presence of comorbid moderate and severe OSA. Nevertheless, patients living with comorbid insomnia and sleep apnea and treated with CBTi should be monitored closely for increased daytime sleepiness during the initial weeks of bedtime restriction therapy. Clinical Trial Registration: Treating comorbid insomnia with obstructive sleep apnoea (COMISA) study: A new treatment strategy for patients with combined insomnia and sleep apnoea, https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id = 365184 Australian New Zealand Clinical Trials Registry: ACTRN12613001178730. Universal Trial Number: U1111-1149-4230.